2008
DOI: 10.1111/j.1751-8369.2008.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

The Upper Triassic of northern Middle Siberia: stratigraphy and palynology

Abstract: The Lower Carnian succession in northern Middle Siberia includes continental and marine deposits. Bivalves, nautiloids and ammonites in the marine units provide biostratigraphic control for a palynological study of three important sections. Palynomorph associations from the base of the succession include forms that have previously been reported only from Norian and Rhaetian deposits in the Tethyan and Boreal realms. This suggests that, in comparison with other areas, the palynoflora of Siberia was more uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
(15 reference statements)
0
8
0
3
Order By: Relevance
“…Kü rschner et al (2007), Lucas & Tanner (2007) and Cirilli et al (2009) agreed with this hypothesis. Similarly, classic Rhaetian taxa of Europe, such as Rhaetipollis germanicus and Zebrasporites spp., extend into the Early Carnian near the Late Triassic North Pole in northern Middle Siberia (Kozur & Weems 2007;Ilyina & Egorov 2008). The idea that the vesicate monosulcate taxa Patinasporites, Enzonalasporites and Vallisporites might be geographically provincial is not completely unconventional.…”
Section: Palynology and Provincialismmentioning
confidence: 99%
See 1 more Smart Citation
“…Kü rschner et al (2007), Lucas & Tanner (2007) and Cirilli et al (2009) agreed with this hypothesis. Similarly, classic Rhaetian taxa of Europe, such as Rhaetipollis germanicus and Zebrasporites spp., extend into the Early Carnian near the Late Triassic North Pole in northern Middle Siberia (Kozur & Weems 2007;Ilyina & Egorov 2008). The idea that the vesicate monosulcate taxa Patinasporites, Enzonalasporites and Vallisporites might be geographically provincial is not completely unconventional.…”
Section: Palynology and Provincialismmentioning
confidence: 99%
“…There is a corresponding time-transgressive shift in facies in continental strata, reflected in vertical successions from red beds and evaporates to grey strata, sometimes with coals in the northern sections. Similarly, classic Rhaetian taxa of Europe, such as Rhaetipollis germanicus and Zebrasporites spp., extend into the Early Carnian near the Late Triassic North Pole in northern Middle Siberia (Kozur & Weems 2007;Ilyina & Egorov 2008). Thus, it is no surprise that the tropics contained floras that differed from the temperate region, or that a flora might be time-transgressive as central Pangea translated northward.…”
Section: Palynology and Provincialismmentioning
confidence: 99%
“…Among Russian publications, Yaroshenko et al (1991) reported on Lower Triassic palynology of the Pechora area. Works on the Upper Triassic include those of Fefilova (1986Fefilova ( , 1988Fefilova ( , 1990 and of Ilyina and Egorov (2008), who published on palynology from the Carnian of Siberia.…”
Section: Uvaesporites Imperialis (Common)mentioning
confidence: 99%
“…Terrestrially derived material, mainly pollen and spores, dominate palynofloras from the Upper Triassic successions of the present Arctic (e.g. Suneby and Hills, 1988;Hochuli et al, 1989;Ilyina and Egorov, 2008;Vigran et al, 2014). However, marine palynomorphs are relatively common in parts of these successions (e.g.…”
Section: The Present Arcticmentioning
confidence: 99%
“…Interestingly, despite the existence of ammonite-dated, fossiliferous marine successions from East Siberia (Russian Arctic) (Dagys et al, 1993, Egorov andMørk, 1998;Konstantinov et al, 2003;Ilyina and Egorov, 2008)…”
Section: Arctic Russiamentioning
confidence: 99%